Why information and transparency about electricity matter: Fragmentation of governance and accountability under New Public Management. Issue 1 (30th October 2019) - Molyneaux, Lynette; Head, Brian
Abstract: From 1995, Australian governments pursued efficiency benefits arising from significant structural reforms in the Electricity Supply Industry, including corporatisation and regulation of network monopolies, and introduction of competition for generators and for retailers. The restructure was motivated by the ideology of New Public Management and influenced by the field of neoliberal economics. More than two decades later, prices paid for electricity by residential and commercial customers have escalated sharply, resulting in sustained anger from all consumers. The Australian Competition and Consumer Commission Chair has admitted that 'The National Electricity Market is largely broken'. This article documents the reduction in public access to information about electricity supply, the fragmentation in responsibility and accountability for consumer outcomes, and the consequences of these changes for transparency, industry operation, and retail electricity prices. New research enabled the creation of a database of Queensland energy production, consumption, and prices; this facilitated a fresh analysis of Queensland electricity sector performance since the restructure of electricity supply. Abstract : This article details the reduction in public access to information about Queensland's electricity supply and fragmentation in responsibility and accountability for consumer outcomes, as a result of NPM reforms in the 1990s, and the consequences of these changes for transparency, industry operation, and retail electricity prices.